1997
DOI: 10.1055/s-2008-1071208
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Dual-Switch Valve for the Treatment of Adult Normotensive or Hypertensive Hydrocephalus

Abstract: Since the beginning of 1995 the new hydrostatic dual-switch valve (DSV) was implanted in 35 adult patients with hydrocephalus of different etiology. 26 patients suffered from normotensive hydrocephalus (10 idiopathic and 16 symptomatic), and 9 patients from hypertensive hydrocephalus of various origin. The first 21 cases of this cohort were compared in a randomized study with a comparable group of 21 hydrocephalic patients who received a conventional differential-pressure (DP-) valve. The clinical status and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…55) Furthermore, one study using an antisiphon device (the dual-switch valve) showed a 3% transient incidence of subdural hygroma and no cases needing operation. 56) In contrast, patency rates for Orbis-Sigma Valve } (Integra NeuroSciences, Sophia Antipolis, France) were lower than for the other tested valves and the rates of operation for subdural hematoma were higher than for the other valves. 66) Other reports of infrequent complications include gastrointestinal and bladder perforations from peritoneal catheters, 34) hearing deficits, 61) and tension pneumocephalus.…”
Section: -B Complicationsmentioning
confidence: 95%
See 2 more Smart Citations
“…55) Furthermore, one study using an antisiphon device (the dual-switch valve) showed a 3% transient incidence of subdural hygroma and no cases needing operation. 56) In contrast, patency rates for Orbis-Sigma Valve } (Integra NeuroSciences, Sophia Antipolis, France) were lower than for the other tested valves and the rates of operation for subdural hematoma were higher than for the other valves. 66) Other reports of infrequent complications include gastrointestinal and bladder perforations from peritoneal catheters, 34) hearing deficits, 61) and tension pneumocephalus.…”
Section: -B Complicationsmentioning
confidence: 95%
“…However, reports have shown that there are no major differences between the valves in terms of complication rates of infection 30,51,55,68) or shunt occlusion. 32,55,56,67) However, the use of antibiotics during the perioperative period has been shown to reduce the incidence of infection. 67) Complications of nontraumatic subdural hygroma/hematoma were reported to improve by resetting to higher pressures in the Codman-Hakim Programmable Valve } and Sophy Valve } , and evacuative operations were only required in 2.7% of cases using the Codman-Hakim Programmable Valve } 51,68) and 1.4% using the Sophy Valve } .…”
Section: -B Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of antisiphon devices reportedly reduces the incidence of subdural effusion, complete prevention cannot be obtained. 107,108) Further, underdrainage of flow may occur. Whether these devices can be recommended for routine use in iNPH is still unsettled (Recommendation grade C).…”
Section: E Antisiphon Devicesmentioning
confidence: 99%
“…133A) Patency rates of shunts at 1 year after operation have been reported to be 75% for CHPVs 133A) and 62% for Orbis-Sigma valves (OSVs), 130) suggesting a slight superiority in efficacy of CHPVs. The incidence of shunt obstruction ranged from 2% 107) to 30% 133) for CHPVs, 4% for SVs, 104) 5% for the dualswitch valves  (DSVs; B Braun, Germany), 107) and 10% for the DPVs. 69A) Although it is difficult to make a direct comparison of these valves due to differences in the observation period, in general, there seemed to be no differences between them.…”
Section: Complicationsmentioning
confidence: 99%